Ports, crime and security governing and policing seaports in a changing world - Sergi, Anna; Storti, Luca Storti; Easton, Marleen; Reid, Alexandria (Bristol shorts research)
The COVID-19 pandemic, Brexit and the US-China trade dispute have heightened interest in the geopolitics and security of modern ports. Applying a multidisciplinary lens to the political economy of port security, this book presents a unique outlook on the social, economic and political factors that shape organised crime and governance.